Montenegro : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper focuses on Montenegro's export sector performance and challenges. Montenegro has run a persistent trade deficit since its independence. Montenegro's goods exports have decreased, while goods imports have been more or less stable. A comparison reveals a relatively weak recovery of goods exports for Montenegro. Montenegro's goods exports to the euro area have declined over time despite euroization. Foreign demand explains services exports well, but less so goods exports. Business climate surveys indicate high nonprice barriers in Montenegro's export sector. The share of high-value-added export goods has been diminishing over time. Services exports also signal narrow productivity gains. Weak productivity growth may hinder the export sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Montenegro